Aortic Aneurysm - Kirali, Kaan (IntechOpen, 2017)
Aortic aneurysms are very silent, insidious, and sudden complicated pathologies with high incidence of sudden death. The aorta has several different parts, which are affected by aneurysmal pathology independently and separately or conjointly. Preventive medicine and determinative genetic heritage are the first steps during diagnosis and precaution. Preventive screening of the general population seems the best way for diagnosing early asymptomatic aneurysms with increased health cost. Because sudden death is the first symptom of aortic aneurysms, early interventional treatment is essential to protect fatal complications. In spite of open surgical repair which is the standard procedure, isolated or hybrid endovascular approaches are used widespread in the last decade due to reduction of procedural complications. This book is composed of the main topics on aortic aneurysms and surgical treatments to extend scientific and therapeutic perspective and vision of cardiac teams.